2020
DOI: 10.18332/tid/125195
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of facilitators and barriers to smoking cessation and tobacco-dependence treatment in patients with tuberculosis in low- and middle-income countries

Abstract: INTRODUCTION Smoking is a substantial cause of premature death in patients with tuberculosis (TB), particularly in low-and middle-income countries (LMICs) with high TB prevalence. The importance of incorporating smoking cessation and tobacco-dependence treatment (TDT) into TB care is highlighted in the most recent TB care guidelines. Our objective is to identify the likely key facilitators of and barriers to smoking cessation for patients with TB in LMICs. METHODS A systematic search of studies with English-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(127 reference statements)
1
4
0
Order By: Relevance
“…Religious factors, such as the observance of the Lent season among Christians and EID among Muslims, have also been found in this study as an important reason for smokers to quit smoking. On the other hand, similar to other studies, it is noted that some of the barriers to smoking cessation found in this study include: strong influence from smoking friends and families 35 ; nicotine addiction [36][37][38] ; accessibility of cigarettes 39 ; misunderstanding that quitting smoking can damage health; lack of support from social networks such as family and friends 39,40 ; misperception and/or misunderstanding that accepting cigarettes from a friend is a token of friendship 41,42 ; and the lack of willpower to refuse a cigarette when being offered by a smoking friend 39 .…”
Section: Discussionsupporting
confidence: 89%
“…Religious factors, such as the observance of the Lent season among Christians and EID among Muslims, have also been found in this study as an important reason for smokers to quit smoking. On the other hand, similar to other studies, it is noted that some of the barriers to smoking cessation found in this study include: strong influence from smoking friends and families 35 ; nicotine addiction [36][37][38] ; accessibility of cigarettes 39 ; misunderstanding that quitting smoking can damage health; lack of support from social networks such as family and friends 39,40 ; misperception and/or misunderstanding that accepting cigarettes from a friend is a token of friendship 41,42 ; and the lack of willpower to refuse a cigarette when being offered by a smoking friend 39 .…”
Section: Discussionsupporting
confidence: 89%
“…A study showed that when developing policies and actions aimed at abstinence from smoking among patients diagnosed with TB, there was a decrease in the rate of diagnoses and deaths after smoking cessation [31]. Thus, after six weeks of smoking cessation, the adverse effects of tobacco on the immune system disappear and contribute to a better clinical evolution of the patient [32].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review pointed out that among facilitators to assist in smoking cessation are repeated brief interventions (including motivational therapy and leaflet distribution), followed by behavioral counseling incorporated into the routine of health care for patients with TB [31].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Aryanpur et al 29 reported that at the time of TB diagnosis, 23.8% of newly diagnosed smoking TB patients quit immediately and 52.4% of patients who continued to smoke had intention to quit during the following month. Other studies also confirmed that the diagnosis of TB was an opportunity for initiating smoking cessation interventions, suggesting that smoking cessation should be adopted into TB care to ensure a successful integration of TB and tobacco control activities 30 - 31 . The finding indicating that women are less receptive to smoking cessation compared to men was consistent with the literature 32 - 35 ; however, in our study this phenomenon was discussed as an opportunity for initiating smoking cessation interventions specifically among Armenian TB patients who are, in fact, predominantly men 10 .…”
Section: Discussionmentioning
confidence: 88%